Identification of Cross-sector Service Utilization Patterns Among Urban Medicaid Expansion Enrollees. Issue 2 (February 2019) - Bodurtha, Peter J.; Winkelman, Tyler; Vickery, Katherine D.; Owen, Ross; Van Siclen, Renee; Erickson, Erik; Hougham, Courtney; Legler, Mark; Jennings, Latasha; Shippee, Nathan
Abstract : Background: The expansion of Medicaid as part of the Affordable Care Act opened new opportunities to provide health coverage to low-income adults who may be involved in other public sectors. Objective: The main objective of this study was to describe cross-sector utilization patterns among urban Medicaid expansion enrollees. Research Design: We merged data from 4 public sectors (health care, human services, housing, and criminal justice) for 98, 282 Medicaid expansion enrollees in Hennepin County, MN. We fit a latent class model to indicators of cross-sector involvement. Measures: Indicator variables described involvement levels within each sector from March 2011 through December 2014. Demographic and chronic condition indicators were included post hoc to characterize classes. Results: We found 6 archetypes of cross-sector involvement: The "Low Contact" class (33.9%) had little involvement in any public sector; "Primary Care" (26.3%) had moderate, stable health care utilization; "Health and Human Services" (15.3%) had high rates of health care and cash assistance utilization; "Minimal Criminal History" (11.0%) had less serious criminal justice involvement; "Cross-sector" (7.8%) had elevated emergency department use, involvement in all 4 sectors, and the highest prevalence of behavioral health conditions; "Extensive Criminal History" (5.7%) had serious criminal justice involvement. The 3 most expensive classes (Health and Human Services, Cross-sector, and Extensive Criminal History) had the highest rates of behavioral health conditions. Together, they comprised 29% of enrollees and 70% of total public costs. Conclusions: Medicaid expansion enrollees with behavioral health conditions deserve focus due to the high cost-reduction potential across public sectors. Cross-sector collaboration is a plausible path to reduce costs and improve outcomes. Abstract : Supplemental Digital Content is available in the text.